Correction: Niederhauser et al. Anti-SARS-CoV-2 Antibody Development over Four Years in Blood Donors. Viruses 2025, 17, 1292 - Niederhauser, Christoph; Widmer, Nadja; Tinguely, Caroline; Suter Riniker, Franziska; Fontana, Stefano; Buser, Andreas; Waldvogel, Sophie; Thierbach, Jutta; Züger, Max; Gowland, Peter (Viruses, 2025)
In the original publication [...]